Besties. find their groove - Miller, Kayla; Canino, Jeffrey; Luu, Kristina; Miller, Kayla (2022)
"With their first formal school dance around the corner, Beth and Chanda are on a mission to make it the best night ever. Step one? Secure the perfect dresses so they can dominate the dance floor! But when neither of them can find an outfit that lives up to their high expectations--and when they encounter unexpected pressure to find dates--these besties will need to lean on their friendship more than ever if they hope to find their groove and bust a move!"--
"From the world of Click"--Cover.
"Based on the Click series, created by Kayla Miller"--Title page verso.
Chiefly illustrations.
Ages 8-12
Keywords: Best friends -- Comic books, strips, etc; Dance parties -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Preteen girls -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Best friends -- Juvenile fiction; Dance parties -- Juvenile fiction; Friendship -- Juvenile fiction; Preteen girls -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Dance parties -- Fiction; Schools -- Fiction; Graphic novels; JUVENILE FICTION / Social Themes / Adolescence & Coming of Age; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Comics & Graphic Novels / Humorous; Best friends; Dance parties; Friendship; Middle schools; Preteen girls; Schools; Comics (Graphic works); Fiction; Juvenile works; Children's stories -- Comic books, strips, etc; School comics; Graphic novels; Comics (Graphic works); Graphic novel adaptations